Assessing the Association of Element Imbalances With Arsenism and the Potential Application Value of Rosa roxburghii Tratt Juice - Xu, Yuyan; Sun, Baofei; Zeng, Qibing; Wei, Shaofeng; Yang, Guanghong; Zhang, Aihua (Frontiers in Pharmacology, 2022)
Endemic arsenism caused by coal burning is a unique type of biogeochemical disease that only exists in China, and it is also a disease of the element imbalances. Previous studies have shown that the element imbalances are involved in the pathogenesis of arsenic; however, the knowledge of the interaction between the various elements and effective preventive measures have not been fully studied. This study first conducted a cross-sectional study of a total of 365 participants, the results show that arsenic exposure can increase the content of elements (Al, As, Fe, Hg, K and Na) in the hair(P<0.05), but the content of other elements (Ca, Co, Cu, Mn, Mo, P, Se, Sr, V and Zn) were significantly decreased(P<0.05). And the high level of As, Fe, Pb and the low level of Se can increase the risk of arsenism (P<0.05). Further study found that that the combined exposure of Fe-As and Pb-As can increase the risk of arsenism, but the combined exposure of Se-As can reduce the risk of arsenism (P<0.05). Particularly, a randomized, controlled, double-blind intervention study reveals that Rosa roxburghii Tratt juice (RRT) can reverse the above-mentioned element imbalances (the high level of Al, As, Fe and the low level of Cu, Mn, Se, Sr, Zn) caused by arsenic (P<0.05). Our study provides some limited evidence that the element imbalances (the high level of As, Fe, Pb and the low level of Se) are the risk factors for the occurrences of arsenism. The second major finding was that RRT can regulate the element imbalances, which is expected to improve the arsenism. This study provides scientific basis for further understanding a possible traditional chinese health food, RRT, as a more effective detoxication of arsenism.